Wirksamkeit des Präventionsprogramms „Keiner fällt durchs Netz“ - Sidor, Anna; Fischer, Cristina; Evers, Oliver; Taubner, Svenja (Psychotherapeut, 2018)
BackgroundDifficult conditions during childhood can impair an individual’s emotional, cognitive, and social development in many ways. The early prevention approach addresses supportive interventions for families in the critical early phase of the transition to parenthood.AimThe effectiveness of the German prevention program “Nobody slips through the net” (KfdN) on support of risk-burdened families was investigated.Material and methodsThe study consisted of a sample of 150 risk-burdened mothers and children who took part in the KfdN program and 152 risk-burdened dyads from control families (CG). The data were collected at five measurement points.ResultsThe level of the children’s social development improved after the intervention in comparison to the CG. Mothers in the KfdN group judged their children as less “difficult” and dysfunctionality of the mother-child interaction was reduced. The results of the 1‑year and 2‑year follow-up showed positive long-term effects in the areas of maternal assessment of the child’s “difficulty” and the parenting behavior.ConclusionThe assignment of specially trained family midwives appears to be useful not only in terms of children’s social development but also in the long-term on the maternal perception of the child and the parenting behavior.